Linking Ecosystem Services, Cultural Identity, and Subjective Wellbeing in an Emergent Cultural Landscape of the Galápagos Islands - Quijozaca, Jenny A.; Aguado, Mateo; González, José A. (Land, 2026)
Punta Carola beach, located on San Cristóbal Island in the Galápagos Archipelago, exemplifies how island environments of recent human settlement can rapidly acquire cultural significance. Drawing on a survey of 201 residents, this study examines perceptions of the ecosystem services provided by Punta Carola, their relationship to subjective wellbeing, and attitudes toward alternative tourism and governance strategies. The findings reveal that the inhabitants of San Cristóbal recognize a wide range of tangible and intangible benefits that the natural environment of Punta Carola contributes to their quality of life, sense of belonging, and cultural identity, as well as recreational and aesthetic values. Life satisfaction was positively associated with perceptions of nature’s contribution, the maintenance of local ecological knowledge, and household income, while formal education correlated negatively. Residents identified freshwater and artisanal fishing as the most critical ecosystem services, reflecting their centrality to local livelihoods and wellbeing. The results also underscore widespread criticism of large-scale tourism projects perceived as exclusionary or unsustainable and highlight the importance of participatory governance schemes that legitimize local values. Punta Carola thus emerges as a “cultural landscape of resistance”, where external pressures catalyze identity construction and territorial rootedness. This case contributes to academic debates on socio-ecological resilience in fragile island contexts and offers actionable insights for inclusive planning in the Galápagos.
Keywords: cultural landscapes; ecosystem services; subjective wellbeing; local ecological knowledge; participatory governance; Galápagos; socio-ecological resilience